If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 * -7 + -1y = 1 Multiply 2 * -7 -14 + -1y = 1 Solving -14 + -1y = 1 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '14' to each side of the equation. -14 + 14 + -1y = 1 + 14 Combine like terms: -14 + 14 = 0 0 + -1y = 1 + 14 -1y = 1 + 14 Combine like terms: 1 + 14 = 15 -1y = 15 Divide each side by '-1'. y = -15 Simplifying y = -15
| a-45=55 | | f(x)=2f+6f | | 2*0-y=1 | | ln(x)+ln(3)=ln(4) | | 15x=-24 | | 2(x+1)/3=5x-3 | | x+y+z=20 | | 5a/4b^2-16b/25a^2 | | (4x^2-9)/(2x+3) | | -5(4y)-5+2(7y+8)= | | 2x^2/3-3x^1/3-20=0 | | 9d^2+24d+12=0 | | 4x(x-2)-3x(x+1)=-18 | | -11y=15-6t | | 7x^2y+4xy^2-7yx^2+5-6y^2x= | | y-24=37-20 | | 73-3x=7x+22 | | 2x^2/3-7x^1/3+6=0 | | x+6=3x-18 | | ln(x-6)+ln(5)=ln(30) | | 3nsquared=75 | | 5y+10x=15 | | 3(2x-7)-2(x-3)=-9 | | .70x+.40y=60 | | -6x^2-4x=22 | | 5c(c+d)= | | 8x+2=9-6 | | 160-2x=43x+20 | | -6*(-6)= | | 1/4(5x-3)=8 | | 8x+4=3x-11 | | (4/9)^-2 |